Verification of intimate and non-intimate recovery of DNA within Sexual Assault Referral Centres (SARCs) - Michelle Gaskell; June Guiness; Amy Hamm; Guylaine O. Hanford; Abi Marshall; Kevin Sullivan (Forensic Science International: Synergy)
This paper describes the verification of DNA recovery processes undertaken in forensic medical examination facilities within Sexual Assault Referral Centres (SARCs) across England and Wales in the investigation of rape and sexual assault. This is in support of a national initiative for SARCs to provide additional quality assurances regarding forensic integrity. This is achieved through compliance with the Forensic Science Regulator (FSR) Code of Practice including accreditation to ISO 15189 Medical Laboratories: Requirements for Quality & Competence.Existing national Faculty of Forensic & Legal Medicine (FFLM) recommended intimate and non-intimate DNA recovery processes were verified by five SARCs in a pilot study utilising both in vivo and in vitro testing. Three types of recovery scenarios were tested: 1) non-intimate recovery of touch DNA was undertaken from volunteers’ skin following simulated struggles; 2) non-intimate recovery of blood, semen and saliva on simulated skin surfaces; 3) intimate recovery of known semen and saliva donors from gynaecological anatomical models. No contamination issues were observed in the non-intimate sample recovery exercises where the recovery technique is the same for live casework. However, with a minority of the intimate sample recoveries, some iatrogenic transfer of seeded DNA within the models was identified. Root cause analysis of the data led to the development of a new approach for training and known outcome competence assessment in intimate DNA recovery using gynaecological models seeded with invisible UV dyes to detect unintended transfer events. This verification exercise has led to the creation of the first SARC proficiency testing scheme.